2016
DOI: 10.1002/pros.23260
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Seed and Soil: Understanding and Targeting Metastatic Prostate Cancer; Report From the 2016 Coffey–Holden Prostate Cancer Academy Meeting

Abstract: This article reviews the topics presented and discussions held at the CHPCA Meeting, with a focus on the unknowns and next steps needed to advance our understanding of the biology and most effective treatment strategies for metastatic prostate cancer. Prostate 77:123-144, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 173 publications
(202 reference statements)
0
7
0
Order By: Relevance
“…Aside from these rare cases with mismatch DNA repair defects, prostate cancer is considered to have a relatively immunologically “cold” microenvironment compared to other solid tumor types ( 15 , 16 ), however the relationship between lymphocytic infiltration and patient outcomes has varied widely in the literature ( 17 24 ). A few studies have suggested that low numbers of tumor-infiltrating lymphocytes are associated with a higher risk of disease progression ( 17 , 21 ), while most other studies have shown the opposite ( 18 21 , 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from these rare cases with mismatch DNA repair defects, prostate cancer is considered to have a relatively immunologically “cold” microenvironment compared to other solid tumor types ( 15 , 16 ), however the relationship between lymphocytic infiltration and patient outcomes has varied widely in the literature ( 17 24 ). A few studies have suggested that low numbers of tumor-infiltrating lymphocytes are associated with a higher risk of disease progression ( 17 , 21 ), while most other studies have shown the opposite ( 18 21 , 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, three quarters of patients recurring following SBRT to bone-only disease reoccurred in bone, whilst irradiated nodal disease re-occurred only in other nodes. This predilection for recurrence locations manifests the interaction between cancer biology and its microenvironment, a concept described as seed and soil (93). A recent retrospective study of prophylactic nodal treatment found that elective nodal radiotherapy +/− boost, reduces nodal recurrences compared to SBRT (P<0.001), and for patients with a single node this led to a significantly longer metastases-free survival (P=0.009; HR 0.5, 95% CI, 0.3-0.85) (94).…”
Section: Early Datamentioning
confidence: 99%
“…For six consecutive years, PCF has convened the Coffey‐Holden Prostate Cancer Academy (CHPCA) Meeting, an annual “think tank” conference, which gathers ∼75 investigators to discuss the most critical topics necessary for making a near‐term impact on the understanding and treatment of lethal prostate cancer . This meeting is uniquely designed to promote deep and ample discussion and brainstorming of necessary next steps by structuring sessions into short talks with lengthy discussion times.…”
Section: Introductionmentioning
confidence: 99%